RELATIONSHIP OF WATER WHEEL PARAMETERS (Proceedings of International Educators Conference, 2023)
Using the possibilities of renewable energy sources, especially the problem of obtaining electricity using low-pressure water sources, has become an urgent problem today. Because it is they who make up the majority and are found very widely. Places with a water pressure of 4-5 meters are rare. The main part of water sources (channels, collectors, etc.) has a depth of 0.5-3 meters [1]. In rural and mountainous areas, there are many places where you can create a pressure of up to 3 meters on existing water sources. Previously, water wheels were used for irrigation. Today it is important not only to irrigate the fields, but also to receive electricity for remote users, i.e. use these water sources as a source of energy (wheel horizontally or vertically) [2,3].